The determinants of crypto currency price: the case of Bitcoin - Woo, Xue Ling; Boon, Kar Kei; Chee, Pei Jin; Ngee, Zing Yi; Wong, Ke Sin (2019)
This study examines the relationship between the determinants that will affect on the price formation of Bitcoin from period year 2016 Aug 2 to 2018 May 30, which consist of daily data of 239 observations. A theoretical framework is constructed to test on the relationship between the Bitcoin Price determinants with the independent variables which are computational power of Bitcoin miners (hash rate), gold prices, velocity of Bitcoin in circulation (demand-supply fundamentals) and the price of Ethereum as a substitution coin. Autoregressive Distributed Lag (ARDL) is adapted to test on the long run relationship between the determinants. Besides, causality direction, dynamic stability and shocks of the empirical model are examined in this study.